Karakteristik Gaya Komunikasi Presiden Jokowi Dalam Pengambilan Kebijakan - Intyaswati, Drina; Mansur, Mansur (Universitas Muhammadiyah Ponorogo, 2017)
The mass media bring news about the various issues that arise in the community, including those related to communication styles of President Jokowi in communicating policies. The last case, in which ministers make